2019
DOI: 10.3390/jrfm12030148
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Test of Capital Structure Theories for the Vietnamese Listed Firms

Abstract: Raising capital efficiently for the operations is considered a fundamental decision for any firms. Since the 1960s, various theories on capital structure have been developed. Various empirical studies had also been conducted to examine the appropriateness of these theories in different markets. Unfortunately, evidence is mixed. In the context of Vietnam, a rising powerful economy in the Asia Pacific region, this important issue has been largely ignored. This paper is conducted to provide additional evidence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…Kopecky et al (2018) utilized an alternative capital structure policy which was deviant from the Modigliani and Miller (1958) and Miller (1988) theorem for the prediction of borrowing funds that reinstates the irrelevance of the capital structure. The Trade-Off Theory: An investigation on the use of the capital structure theories in 227 Vietnamese listed firms indicated that the trade-off theory was adopted to explain their implemented financial decisions (Nguyen et al, 2019). According to Bajaj et al (2020), a total of 183 research papers were analyzed on the capital structure theories in developing countries, but a lack of primary research still exists.…”
Section: Theories Of Capital Structurementioning
confidence: 99%
“…Kopecky et al (2018) utilized an alternative capital structure policy which was deviant from the Modigliani and Miller (1958) and Miller (1988) theorem for the prediction of borrowing funds that reinstates the irrelevance of the capital structure. The Trade-Off Theory: An investigation on the use of the capital structure theories in 227 Vietnamese listed firms indicated that the trade-off theory was adopted to explain their implemented financial decisions (Nguyen et al, 2019). According to Bajaj et al (2020), a total of 183 research papers were analyzed on the capital structure theories in developing countries, but a lack of primary research still exists.…”
Section: Theories Of Capital Structurementioning
confidence: 99%
“…The internal funding deficit will be financed using a source of funds derived from retained earnings to decrease debt. It is reinforced by the research results of Byoun and Rhim (2003) and Nguyen, Ho, & Vo (2019). A hypothesis could be formulated based on these descriptions, as follows.…”
Section: Pamungkas and Surwantimentioning
confidence: 90%
“…Abdullazade (2019) indicated that firms prefer to use debt financing to fix small financing issues but resort to equity financing for large deficits. The Pecking Order Theory explains the capital structure decision and financing behaviour of firms (Nguyen, Ho, and Vo, 2019). Since most SMEs are challenged with securing funds (access to finances) and skills to managing those funds (financial awareness, accounting skills and budgeting skills) to ensure SME's financial stability, it is significant to look at factors that guarantee access to funds as well as factors affecting the effective management of these funds.…”
Section: Theoretical Framework: Pecking Order Theorymentioning
confidence: 99%